2011
DOI: 10.1111/j.1447-0594.2011.00767.x
|View full text |Cite
|
Sign up to set email alerts
|

First prescription of new elderly patients attending the psychiatry outpatient of a tertiary care institute in North India

Abstract: Olanzapine, SSRI and clonazepam were the most commonly prescribed antipsychotic, antidepressant, and benzodiazepine, respectively, and valproate was preferred over lithium among elderly patients with bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…AUDIT (Dhupdale et al, 2006;Ghosh et al, 2012), MAST (Ray & Chandrasekhar, 1982) and CAGE (Deswal et al, 2008;Seby et al, 2011). Three studies relied on clinical diagnosis made as per ICD 9 or 10 (Grover et al, 2011;Selvaraj et al, 1997;Tiwari & Srivastava, 1998). One study used 'clinical diagnosis' to assess AUD but did not specify whether this was using standardised criteria (Rao & Madhavan, 1982).…”
Section: Diagnostic Criteria and Structured Instruments (Table 2)mentioning
confidence: 99%
See 2 more Smart Citations
“…AUDIT (Dhupdale et al, 2006;Ghosh et al, 2012), MAST (Ray & Chandrasekhar, 1982) and CAGE (Deswal et al, 2008;Seby et al, 2011). Three studies relied on clinical diagnosis made as per ICD 9 or 10 (Grover et al, 2011;Selvaraj et al, 1997;Tiwari & Srivastava, 1998). One study used 'clinical diagnosis' to assess AUD but did not specify whether this was using standardised criteria (Rao & Madhavan, 1982).…”
Section: Diagnostic Criteria and Structured Instruments (Table 2)mentioning
confidence: 99%
“…In the rest of the studies conducted in samples with adults over 50 years, the proportion of females ranged from 22% (Arora & Bedi, 1989) to 63.9% (Vedantam et al, 2010). The selected studies include those conducted on participants exclusively aged more than 50 years (Arora & Bedi, 1989), 60 years and above (Alam & Karan, 2011;Chowdhury & Rasania, 2008;Goswami et al, 2005a;Goswami et al, 2005b;Grover et al, 2011;Khokhar & Mehra, 2001;Kumar, Sivan, Reghu, Das, & Kutty, 1994;Medhi et al, 2006;Mutharayappa & Bhat, 2008;Pandve & Deshmukh, 2010;Purty et al, 2006;Rao & Madhavan, 1982;Tiwari & Srivastava, 1998;Vedantam et al, 2010), 65 years and above (Jotheeswaran et al, 2010;Seby et al, 2011;Srinivasan et al, 2010) and larger age groups but with segregated data presented for those over 50 years (Deswal et al, 2008;Dhupdale et al, 2006;Ghosh et al, 2012;Gupta et al, 2005;Gupta et al, 2003 Aging & Mental Health 981 Note: R -rural, U -urban, M -male, F -female, C -community, H -hospital, NS -not specified.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It is also confirmed this evolution in specific studies on psychotropic drugs use pattern in India [16][17][18] . Grover et al, [38] in a study conducted in India, have confirmed that the most commonly prescribed antipsychotic medication is olanzapine (20.7% of patients with an organic mental disorder, 40.8% with psychotic disorder, 30.2% with bipolar disorder); quetiapine and risperidone were the other commonly prescribed antipsychotics.…”
Section: Discussionmentioning
confidence: 96%
“…About half of the subjects were receiving more than one antipsychotic . In a recent study, Grover et al (2012c) evaluated the first prescription handed over to more than 10,000 patients attending the psychiatry outpatient clinic of a tertiary care hospital. Irrespective of the diagnosis, olanzapine was the most commonly prescribed antipsychotic, followed by risperidone.…”
mentioning
confidence: 99%